Gene‐dosage effect of Pfkfb3 on monocyte/macrophage biology in atherosclerosis. (3rd August 2022) - Guo, Shuai; Li, Anqi; Fu, Xiaodong; Li, Zou; Cao, Kaixiang; Song, Mingchuan; Huang, Shuqi; Li, Ziling; Yan, Jingwei; Wang, Litao; Dai, Xiaoyan; Feng, Du; et al.
Abstract : Background and Purpose: Macrophage‐rich atherosclerotic arteries are highly active in glycolysis. PFKFB3, a key glycolytic enzyme, has emerged as a potential therapeutic target in atherosclerosis. Small‐molecule inhibitors of PFKFB3, such as 3PO and PFK158, have demonstrated efficacy in hampering atherogenesis in preclinical models. However, genetic studies elucidating the role of Pfkfb3 in atherogenesis need to be conducted to validate pharmacological findings and to unveil potential pharmacological side effects. Experimental Approach: Apoe −/− mice with global heterozygous or myeloid cell‐specific Pfkfb3 deficiency were fed a Western diet (WD), after which atherosclerosis development was determined. Monocyte subsets in atherosclerotic mice and patients were examined by flow cytometry. Monocyte infiltration was assayed by a Ly6C hi monocyte‐specific latex labelling procedure. In situ efferocytosis was assessed on mouse aortic root sections. Additionally, metabolic status, macrophage motility, efferocytosis, and involved mechanisms were analysed in peritoneal macrophages. Key Results: Global heterozygous or myeloid cell‐specific Pfkfb3 deficiency reduced atherogenesis in Apoe −/− mice. Mechanistic studies showed that PFKFB3 controlled the proliferation and infiltration of proinflammatory monocytes. Moreover, PFKFB3 expression was associated with inflammatory monocyte expansion in patients with atherosclerotic coronary artery disease. Surprisingly, homozygous loss of Pfkfb3 impaired macrophage efferocytosis and exacerbated atherosclerosis in Apoe −/− mice. Mechanistically, PFKFB3‐driven glycolysis was shown to be essential for actin polymerization, thus aiding the efferocytotic function of macrophages. Conclusion and Implications: Collectively, these findings suggest the existence of a double‐edged sword effect of myeloid PFKFB3 on the pathogenesis of atherosclerosis and highlight the need for caution in developing anti‐atherosclerotic strategies that target PFKFB3.